Hearing the voices of Ukrainian refugee women in Italy to enhance empowerment interventions. - Guidi, Elisa; Tosti, Anna Enrica; Meringolo, Patrizia; Hatalskaya, Halina; Chiodini, Moira (American Journal of Community Psychology, 2025)
The 2022 Russian invasion displaced millions of Ukrainians, many of whom sought refuge in Italy. War refugees face heightened mental‐health risks but can also activate resilience and empowerment. This study employed the Transtheoretical Model of Empowerment and Resilience (Brodsky & Cattaneo, 2013) to explore resilience and empowerment processes implemented by Ukrainian refugee women in Italy to cope with war‐related challenges and living in a new country. Twenty Ukrainian refugee women completed questionnaires and participated in semi‐structured interviews. Results indicated perceived psychological distress following traumatic war experiences. Utilizing individual and shared resources, respondents enacted resilience processes stemming from the context of risk in their home country and the receiving country but not empowerment actions. However, some mentioned empowerment goals, such as changes in the formal support system for refugees and creating a network of Ukrainian refugees for mutual support. Results highlighted how some participants held individual characteristics of relative privilege, which could be crucial for transitioning from resilience to empowerment. The study suggests that facilitating this transition may require tailored interventions for the specific needs of Ukrainian refugee women and community‐based interventions for promoting access to shared opportunities with the local community and other migrants. Highlights: Respondents adapted to, withstood, and resisted the context of risk through resilience processes.Individual relative privilege could potentially facilitate the transition to empowerment.Tailored and community‐based interventions may ease that transition from resilience to empowerment.